Effects of Image Preprocessing on Face Matching and Recognition in Human Observers. Issue 6 (11th November 2013) - Liu, Chang Hong; Chen, Wenfeng; Han, Hu; Shan, Shiguang
Summary In person identification, recognition failure due to variations of illumination is common. In this study, we employed image‐processing techniques to tackle this problem. Participants performed recognition and matching tasks where the face stimuli were either original images or computer‐processed images in which shading was weakened via a number of image‐processing techniques. The results show that whereas recognition accuracy in a memory task was unaffected, some of the techniques significantly improved the identification performance in a face‐matching task. We conclude that relative to long‐term face memory, face matching is more susceptible to discrepancy of shading in different images of a face. Reducing the discrepancy by certain preprocessing techniques can facilitate person identification when original face images contain large illumination differences. Copyright © 2013 John Wiley & Sons, Ltd.